Genome-based classification and phylogenetic revision of the family Colwelliaceae with proposals for new genera and species - Lee, Min Seo; Yang, Sung-Hyun; Kim, Yun Jae; Park, Yeong-Jun; Park, Mi-Jeong; Kwon, Kae Kyoung (Frontiers in Ecology and Evolution, 2025)
IntroductionPsychrophilic marine bacteria belonging to the family Colwelliaceae have garnered increasing industrial and ecological interest. However, their phylogenetic positions remain ambiguous when classified solely based on 16S rRNA gene sequences, limiting accurate taxonomic resolution.MethodsTo resolve these ambiguities, we characterized four newly isolated species using a comprehensive taxogenomic framework. We analyzed genome-based indices, including average nucleotide identity (ANI), digital DNA–DNA hybridization (dDDH), and average amino acid identity (AAI), across all publicly available Colwelliaceae genomes. Genus-level AAI thresholds were established through repetitive clustering and evaluation strategies.ResultsOur analysis revealed that genus-level AAI values within Colwelliaceae ranged from 74.07% to 75.11%. Based on these thresholds, we re-evaluated 47 species, including the four novel isolates, and proposed the establishment of 18 new genera, expanding the current taxonomy from 6 to 24 genera. The four novel species were assigned to three of these newly proposed genera.DiscussionThis study presents a revised classification of the family Colwelliaceae grounded in genome-based taxonomic metrics. Our findings highlight the limitations of traditional 16S rRNA-based phylogenies and support the use of taxogenomic approaches to achieve higher taxonomic resolution in marine microbial lineages.